LSRV - Laboratório de subestimação em realidade virtual: uma plataforma de ensino para o curso de Engenharia Elétrica - Jaguaribe, Daniel Rebouças (2024)
In recent decades, the electricity sector has undergone major structural and technological changes, requiring professionals with multidisciplinary training and practical experience. These factors, along with student dropout rates and the COVID-19 pandemic, have driven the updating of engineering curricula, integration between academia and industry and the adoption of new technologies in teaching and learning. In this context, the use of Virtual Reality (VR) in engineering education has grown due to its technological evolution, cost reduction and ability to create customizable and low-cost environments. This work proposes advances in the modeling, implementation, application and validation of a Substation Laboratory in Virtual Reality (LSRV) for teaching substations in electrical engineering courses at the Federal University of Ceará (UFC). Based on the 69-13.8 kV substation projects at UFC’s Professor Prisco Bezerra University Campus, the VLSI has been used for the last three years in two subjects: Generation, Transmission and Distribution and Protection of Electric Power Systems. Among the LSRV’s requirements are: free movement in the substation, verisimilitude, comparison between elements and symbols in the real single-line diagram with the VR environment and the use of simulations. To develop the LSRV, Blender and Unity software were used, with the C# programming language. Blender was used to create three-dimensional models of the objects and Unity to build the interaction scenarios and physics of the environment. To validate LSRV, tests were carried out in pilot classes to check the best teaching strategy and in final classes to confirm the effectiveness of the methodology. Quantitative and qualitative mechanisms were used to evaluate the teaching tool, showing that the proposed methodology, together with the use of VLSI, improves academic performance, as well as increasing student interest and engagement.